Case report Clinical and neuropathological picture of ethylmalonic aciduria – diagnostic dilemma - Jamroz, Ewa; Paprocka, Justyna; Adamek, Dariusz; Pytel, Justyna; Szczechowska, Katarzyna; Grabska, Natalia; Malec, Michalina; Głuszkiewicz, Ewa; Daab, Michał; Wodołażski, Anatolij (Folia Neuropathologica, 2011)
Increased ethylmalonic acid (EMA) in urine is a non-specific finding, and is observed in a number of inborn errors of metabolism, as well as in individuals who carry one of two common polymorphisms identified in the SCAD coding region. The authors present an 8-month-old girl with a suspicion of neuroinfection, although the clinical presentation led to diagnosis of ethylmalonic aciduria. From the neuropathological point of view the most remarkable changes were observed in the brain cortex, which was diffusely damaged practically in all regions of the brain. Of note, the most severe destruction was observed in the deepest regions of the sulci. The cortex of the affected regions showed no normal stratification and its structure was almost totally replaced by a form of “granulation tissue” with a markedly increased number of capillaries. To the authors’ knowledge this is the first clinical report of ethylmalonic aciduria with brain autopsy findings.